Aktualisasi Iman dan Taqwa Terhadap Penggunaan Smartphone di Kalangan Mahasiswa - Muhamad Parhan; Devi Indah Nur'aeni Lukman; Anggi Anggella Hikhmalia; Asri Ananda Afsari A Rosid (IAIN Padangsidimpuan, 2020)
This study aims to explore and examine information about the actualization of faith and piety in smartphone users. This research approach uses a qualitative approach to the method of library study, to know and understand the above phenomena in actual and theoretical terms. Data collection techniques and information in this study using questionnaire instruments and literature studies. The findings of this study are ways to actualize faith and piety in the use of smartphones and the impact of their use as a description or reference for the community to increase one's faith and piety in using smartphones to be more useful and far from mudharat. As for the background of this writing because given the concern over the swift flow of technology (smartphones) that enter and animate every user is not just a means of communication but encourages the formation of an individualist society and loss of identity (faith and piety). So we examine things that will help actualize faith and piety towards smartphone use among the public